Предмет: Математика,
автор: Аноним
Упростить:
6х+19х+26х,При х=5
3*(х+5)+7х,При х=4
7х+21х+32х,При х=4
6х+4*(2х+7),При х=3
Ответы
Автор ответа:
0
6х+19х+26х=51х
если х=5, то 51х=51*5=255
3*(х+5)+7х=3х+15+7=3х+22
если х =4, то 3х+22=3*4+22=12+22=34
7х+21х+32х=60х
если х-4, то 60х=60*4=240
6х+4*(2х+7)=6х+8х+28=14х+28
если х=3, то 14х+28=14*3+28=42+28=70
если х=5, то 51х=51*5=255
3*(х+5)+7х=3х+15+7=3х+22
если х =4, то 3х+22=3*4+22=12+22=34
7х+21х+32х=60х
если х-4, то 60х=60*4=240
6х+4*(2х+7)=6х+8х+28=14х+28
если х=3, то 14х+28=14*3+28=42+28=70
Похожие вопросы
Предмет: Информатика,
автор: tanya8027
Предмет: Физика,
автор: kirill76678
Предмет: Қазақ тiлi,
автор: kamila6019
Предмет: Алгебра,
автор: Аноним